Entorno virtual de aprendizaje para mejorar el proceso de enseñanza – aprendizaje de la disciplina de informática aplicada para los estudiantes de los terceros años del bachillerato general unificado de la unidad educativa San Pedro de Guanujo, cantón Guaranda, provincia Bolívar en el periodo 2023 – 2024. - Chimborazo Lucintuña, Lourdes Piedad (2024)
In this technological project of degree which was carried out in the Educational Unit San Pedro de Guanujo, of the canton of Guaranda, of the Province of Bolívar. It was developed in order to investigate fundamental aspects of the virtual environment in the teaching-learning process in which outstanding learning results were obtained in the students of the third years of unified general baccalaureate. It is considered of great importance to carry out virtual courses with current content taught in the educational establishment. Currently, teachers and students do not put much into practice in Virtual Learning Environments due to the lack of training, dedication and responsibility of the teacher. For which it is used as a mediator "Virtual Learning Environment" that allows to propose a proposal with virtual classrooms created that help to develop and guide behavior, discipline and emotions in the psychological part and cognitive development to put more emphasis on the management of Virtual Environments. Data collection instruments were applied, such as a survey addressed to the 90 students and an interview with the teacher, therefore, the analysis and interpretation of results was carried out. The study is meticulous in person with its own criteria, which can be found throughout this process of inquiry, therefore, relevant and indispensable topics and subtopics in the educational field were observed. In which it was examined in bibliographic sources with other authors who propose their own arguments related to the subject with good teachings and experiences that allow strengthening knowledge in the professional context. Through the proposal, it was observed that the students appreciated the coexistence of participating with the tasks, resources, and activities in the virtual learning environments. 18 Finally, it is favorable that teachers put into practice this innovative technological project so that the educational environment is more dynamic in the authors of education, where they use new teaching-learning methodologies to benefit the development of acquired competencies by students with analytical thinking that allows them to develop in Virtual Learning Environments.